Antioxidant and Antibacterial Properties on Different Tissues of Syzygium Aromaticum - Tan, Suat Hian; Dhurga, Devi Rajaratanam (2013)
This paper focuses on the effect of three drying treatment (microwave-, oven- and air-drying) on the antioxidant and antibacterial properties on different tissues of syzygium aromaticum.